ORIGIN AND EVOLUTION OF LINUM USITATISSIMUM L. - S. N. Kutuzova; E. A. Porokhovinova; G. I. Pendinen (Труды по прикладной ботанике, генетике и селекции)
A complete cyclic crossing between representatives of different taxa of cultivated flax (Linum usitatissimum L.), including its primitive forms, and the wild spccies L. angustifolium Huds. was carried out, and hybrid progeny was studied. On the basis of the similarity of morphological features, and the ability to cross with each other and with the species L. angustifolium and L. usitatissimum ssp. bienne (Mill.) Stankev. with viable progeny, it was suggested that L. angustifolium had been the ancestor of Colchian flax, from which the linseed, intermediate and finally fibre forms consequentially evolved. The ancestor of L. usitatissimum ssp. bienne could be L. angustifolium , as the female form, or Colchian flax. For large-seeded flax and L. crepitans Dum., the ancestor could be the intermediate flax; for the dwarf flax, the crown flax. Winter flax is a form of the conventional oilseed flax sown before the start of the winter season in the areas with mild climate.